Paraneoplastic Sweet's syndrome - Daniela Gomes Cunha; Gabriella Campos-; Julia Macchione Marujo; Gustavo Costa Verardino (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Sweet's syndrome is a rare dermatosis with little-known pathogenesis, associated with some clinical conditions such as infections, autoimmune diseases, inflammatory bowel diseases, vaccination, medications and neoplasms. Hematologic malignancies are the diseases most related to paraneoplastic Sweet's syndrome, but this clinical entity can also be found occasionally in some solid tumors, including genitourinary tract tumors. We report a rare case of paraneoplastic Sweet's syndrome associated with the diagnosis of cervical cancer.